Efektivitas Penyelesaian Pengaduan Masyarakat Melalui Aplikasi Layanan Aspirasi Pengaduan Online Rakyat (Lapor) Di Lingkungan Kementerian Dalam Negeri Republik Indonesia - MZ, Dwi Kurniawan; Syafri, Wirman; Amalia, Rizki (UIR Press, 2024)
The utilization of the National Public Service Complaint Management System/People's Online Aspiration and Complaints Service (SP4N LAPOR) within the Ministry of Home Affairs (Kemendagri) has been implemented since 2018. Currently, the management of public complaints has also been formalized in Minister oh Home Affairs Regulation Number 8 of 2023 concerning Complaints Management within the Ministry of Home Affairs and Regional Governments. However, the utilization of the LAPOR application to accommodate public reports or complaints within Kemendagri has thus far not reached its maximum potential. The LAPOR application within Kemendagri is underutilized by the general public and government officials. Given the aforementioned issues, this research aims to explore the effectiveness of resolving public complaints through the LAPOR application within the Ministry of Home Affairs, identify emerging barriers in its resolution, and ascertain efforts made to address these barriers. This study adopts a qualitative method with a descriptive approach. To evaluate effectiveness, this research is grounded in the DeLone and McLean theory encompassing Information Quality, System Quality, User, User Satisfaction, Individual Impact, and Organizational Impact. The findings of this study indicate that the utilization of the LAPOR application within Kemendagri can be deemed effective in facilitating and resolving public reports. However, there remains dissatisfaction among the public regarding the responsiveness or answers to complaints, partly attributed to personnel rotations. The application system has successfully enhanced efficiency, albeit with some reports still being submitted through direct channels. Overall user satisfaction levels, as assessed through satisfaction ratings, are fairly good, and application integration has improved the quality and efficiency of complaint handling. The study also identifies several barriers in managing complaints through the LAPOR application, including human resource limitations, budget constraints, application features and accessibility, insufficient socialization, and lack of coordination among components. To address these challenges, the Directorate of Complaints Facilitation and Information Management (FPPI) of the Ministry of Home Affairs has undertaken various efforts, including monitoring and evaluation assistance, regulatory improvements, and external cooperation and coordination.